Penyuluhan Pemanfaatan Obat Tradisional dan Pembuatan Hand Sanitizer dalam Pencegahan Covid-19 di Masyarakat Pulau Hiri - Amran Nur Amran; Ismail Rahman (Jurnal Pengabdian UntukMu NegeRI, 2020)
Hiri Island is located in the north of Ternate Island, internet access on the island is still lacking. This has an impact on the lack of information obtained by the people on Hiri Island, including information about the Covid-19 outbreak. the world health organization (WHO) stated that on January 30, 2020, the world had a Corona Virus Pandemic (Covid-19). Hiri Island has a variety of plants, so it is necessary to provide counseling to the community in the area regarding the use of natural ingredients as a traditional medicine in preventing transmission of the coronavirus, as well as providing information about the process of transmission of the virus, one of which transmission media is through hands. So it is necessary to make a handwashing product (hand sanitizer) to prevent transmission of the virus through hand media. In the implementation of the service, there was a change in the method, which initially socialization by gathering the community was changed to direct distribution of hand sanitizers as well as a short explanation to the public about the importance of hand hygiene and the importance of maintaining health by utilizing herbal medicines around the community.